AB0239 Dkk1 is not associated with inflammatory activity indexes in rheumatoid arthritis, but with functional disability related to the long evolution of the disease. (15th June 2017) - Giraldo-Bustos, R; Saldarriaga, EL; Santos, AM; Angarita, JI; Ballesteros, JG; Rueda-Sanchez, JC; Vasquez, A; Valero, L; Arias, S; Londono, J; ,
Abstract : Background: Rheumatoid arthritis (RA) is a systemic chronic inflammatory disease characterized by joint destruction, deformity, lower functional status and decrease in life expectancy. Wnt signaling pathway recently it has been implicated in bone homeostasis. Studies suggest that overexpression of inhibitors of the way, like the Dickkopf 1 protein (DKK1) has been implicated in bone destruction Objectives: To compare circulating levels of DKK1 in patients with RA to their disease activity and functional status Methods: 379 consecutive patients with early and established RA were evaluated at the Hospital Militar Central in Bogota-Colombia, between March 2015 and November 2016. A complete medical history related to RA was obtained. Disease activity was evaluated by DAS28-CRP, CDAI, SDAI and RAPID3. functional status was measurement using MDHAQ and the Steinbrocker functional classification. DKK1 levels measured by ELISA using an Abcam® kit Results: The mean age was 60, 7±13, 1 years, disease duration 13, 1±10, 9 years, 80, 4% were female. Higher levels of DKK1 were not associated with higher disease activity by CDAI (p=0, 70), SDAI (p=0, 84), DAS28 with CRP (p=0, 80) or RAPID3 (p=0, 70). Interestingly Higher levels of DKK1 were significantly associated to greater disability and lower functional status according to the Steinbrocker functional grading (p=0.013) and with severe disability by MDHAQ (p=0.004), Table 1. Other variables associated with joint destruction were osteoporosis, elevated rheumatoid factor, smoking, and hospitalization Conclusions: Higher levels of DKK1 were found in patients with lower functional status. This association was not found in patients with greater disease activity according to CDAI, SDAI, DAS28 and RAPID3. This could be explaining by greater structural damage though more studies would be needed to explore this possibility References: Huizinga TW, Pincus T. In the Clinic. Rheumatoid arthritis. Ann Intern Med. 2010 Jul 6;153(1):ITC1–1-ITC-15. Disclosure of Interest: None declared